A Smart Drone-Based Solution for Natural Disaster Management and Emergency Response - Md. Safaet, Hossain; Motaleb, Hossain; Md., Ebrahim; Redoneul Karim, Abid; Md Hemaet, Uddin (INTI International University, 2025)
Natural disasters present a major global challenge, often leaving millions in urgent need of aid. Floods disrupt transportation routes, delaying critical relief. As such events intensify, traditional emergency response systems face growing limitations. This research investigates how intelligent unmanned aerial systems (UAS) can enhance disaster response, especially when ground access is compromised. Focusing on flood scenarios, it evaluates how aerial platforms improve situational awareness, speed up search efforts, and enable targeted aid delivery. Using case studies and qualitative analysis, the study finds that UAS can reduce response times by 65–80%, deliver 2–4 kg of medical supplies to isolated areas, and provide detailed damage assessments via advanced imaging. A proposed cloud-integrated architecture connects aerial operations with analytical tools for coordinated emergency management. Despite challenges like limited flight endurance and environmental constraints, the system offers a scalable solution for humanitarian logistics in resource-constrained settings. This work contributes practical insights into deploying aerial technologies for disaster relief and outlines strategies to enhance autonomous capabilities and inter-agency coordination.